Understanding Children's Personal Lives and Relationships - Davies, Hayley. author. aut Link
VII, 224 p.
Keywords: Informed by ethnographic research with children, Davies offers new sociological insights into children's personal relationships, as well as closely examining methodological approaches to researching with children and researching relationships.